The Linux Programming Interface - Michael Kerrisk (No Starch Press, 2010)
The Linux Programming Interface is the definitive guide to the Linux and UNIX programming interface—the interface employed by nearly every application that runs on a Linux or UNIX system.In this authoritative work, Linux programming expert Michael Kerrisk provides detailed descriptions of the system calls and library functions that you need in order to master the craft of system programming, and accompanies his explanations with clear, complete example programs.You'll find descriptions of over 500 system calls and library functions, and more than 200 example programs, 88 tables, and 115 diagrams. You'll learn how to:Read and write files efficientlyUse signals, clocks, and timersCreate processes and execute programsWrite secure programsWrite multithreaded programs using POSIX threadsBuild and use shared librariesPerform interprocess communication using pipes, message queues, shared memory, and semaphoresWrite network applications with the sockets APIWhile The Linux Programming Interface covers a wealth of Linux-specific features, including epoll, inotify, and the /proc file system, its emphasis on UNIX standards (POSIX.1-2001/SUSv3 and POSIX.1-2008/SUSv4) makes it equally valuable to programmers working on other UNIX platforms. The Linux Programming Interface is the most comprehensive single-volume work on the Linux and UNIX programming interface, and a book that's destined to become a new classic.Praise for The Linux Programming Interface "If I had to choose a single book to sit next to my machine when writing software for Linux, this would be it." Martin Landers, Software Engineer, Google "This book, with its detailed descriptions and examples, contains everything you need to understand the details and nuances of the low-level programming APIs in Linux . . . no matter what the level of reader, there will be something to be learnt from this book." Mel Gorman, Author of Understanding the Linux Virtual Memory Manager "Michael Kerrisk has not only written a great book about Linux programming and how it relates to various standards, but has also taken care that bugs he noticed got fixed and the man pages were (greatly) improved. In all three ways, he has made Linux programming easier. The in-depth treatment of topics in The Linux Programming Interface . . . makes it a must-have reference for both new and experienced Linux programmers." Andreas Jaeger, Program Manager, openSUSE, Novell "Michael's inexhaustible determination to get his information right, and to express it clearly and concisely, has resulted in a strong reference source for programmers. While this work is targeted at Linux programmers, it will be of value to any programmer working in the UNIX/POSIX ecosystem." David Butenhof, Author of Programming with POSIX Threads and Contributor to the POSIX and UNIX Standards ". . . a very thorough—yet easy to read—explanation of UNIX system and network programming, with an emphasis on Linux systems. It's certainly a book I'd recommend to anybody wanting to get into UNIX programming (in general) or to experienced UNIX programmers wanting to know 'what's new' in the popular GNU/Linux system." Fernando Gont, Network Security Researcher, IETF Participant, and RFC Author ". . . encyclopedic in the breadth and depth of its coverage, and textbook-like in its wealth of worked examples and exercises. Each topic is clearly and comprehensively covered, from theory to hands-on working code. Professionals, students, educators, this is the Linux/UNIX reference that you have been waiting for." Anthony Robins, Associate Professor of Computer Science, The University of Otago "I've been very impressed by the precision, the quality and the level of detail Michael Kerrisk put in his book. He is a great expert of Linux system calls and